2015
DOI: 10.3109/15622975.2015.1073855
|View full text |Cite
|
Sign up to set email alerts
|

The relation between schizotypy and early attention to rejecting interactions: The influence of neuroticism

Abstract: Objectives: Schizotypy relates to rejection sensitivity (anxiety reflecting an expectancy of social exclusion) and neuroticism (excessive evaluation of negative emotions). Positive schizotypy (e.g., perceptual aberrations and odd beliefs) and negative schizotypy (e.g., social and physical anhedonia) could relate to altered attention to rejection because of neuroticism. Methods: Forty-one healthy individuals were assessed on positive and negative schizotypy and neuroticism, and event-related potentials during r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 102 publications
1
23
0
Order By: Relevance
“…The findings emphasise the need for people with schizotypal traits to have more social support and inclusion to overcome social anxiety and social avoidance. Some people with schizotypal traits have families who express criticism and hostility (Premkumar et al, 2015) and communicate poorly (Zborowski and Garske, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings emphasise the need for people with schizotypal traits to have more social support and inclusion to overcome social anxiety and social avoidance. Some people with schizotypal traits have families who express criticism and hostility (Premkumar et al, 2015) and communicate poorly (Zborowski and Garske, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Schizotypal traits denoting social avoidance, that is negative schizotypy, are associated with lower extraversion and agreeableness (Kwapil et al, 2008;Swamih et al 2011). Neuroticism could relate to RS (Berenson et al, 2009), but also mediate the link between negative schizotypy and RS by increasing early attention to rejection scenes, as defined by the P300 eventrelated potential (Premkumar et al, 2015). This finding means that RS could relate to avoidance of social situations when it is accompanied by worrying about social interaction.…”
Section: Social Quality Of Life (Qol) Could Explain the Relation Betwmentioning
confidence: 99%
“…Also, uncertainties about upcoming events or their performance may create considerable discomfort for more neurotic individuals (Gray & McNaughton, 2000). Higher neuroticism scores have been related to increased P2 and P3 amplitudes (Premkumar, et al, 2015), and a larger feedback-related negativity (FRN) in response to uncertain feedback compared to positive or negative feedback (Hirsh & Inzlicht, 2008). Whereas personality traits were associated with both performance and ERPs in the two younger age groups in our study, no significant correlations were found for the Early 30s group.…”
Section: Discussionmentioning
confidence: 99%
“…If schizotypy is actually a looser collection of relatively independent vulnerabilities, any single grouping variable may obscure them all. This is a widely recognized problem in schizophrenia research and has influenced dimensional approaches to schizotypy research . Similarly, group differences in overall cognitive efficiency may interact with differences in the demands of the eliciting stimulus conditions, further obscuring individual differences.…”
Section: Electrophysiological Correlates Of Social Cognition In Subclmentioning
confidence: 99%
“…This is a widely recognized problem in schizophrenia research 47,48 and has influenced dimensional approaches to schizotypy research. 38,39 Similarly, group differences in overall cognitive efficiency may interact with differences in the demands of the eliciting stimulus conditions, further obscuring individual differences. The solutions to this problem are (1) a within-group correlational design sensitive to individual differences in ERPs, cognition and social functioning, within a broadly defined schizotypal sample representing a range of schizotypal characteristics, and (2) a minimaldemand eliciting task, requiring only passive attention to eliciting stimuli.…”
Section: Electrophysiological Correlates Of Social Cognition In Subclmentioning
confidence: 99%